Caracterização de nicho de Sporophila spp. (aves: Emberizidae) e sua relação com a estrutura de microhabitat em áreas de vereda de Uberlândia, MG - Silva, Daniela Beatriz Lima e (2009)
The relative importance of each environmental factor in structuring birds community seems to be variable, and each species exhibits a distinct and specific response to environmental characteristics and their changes. Some granivorous birds can perform seasonal migrations in search of good seeds. They often include the brazilian cerrado, both for breeding and feeding. Little is known about these seasonal movements and the impact that they suffer from habitat degradation of origin and destination areas. Therewith, studies that seek to know the ways of habitats use by these species are very important. This research sought to obtain data on abundance of Sporophila species in Reserva Vegetal do Clube Caça e Pesca Itororó and Estação Ecológica do Panga (Uberlândia, MG), linking it to characteristics of microhabitats, finding differences and similarities in their patterns of environment use and its physical dimensions. For this, 22 points were established along palm swamp areas, which were structurally characterized and used for collection of abundance and use of habitat data, for Sporophila. Morphological measures of length, beak, wing and tarsus were obtained in bird collections and correlated with the behavior of birds. We recorded the species S. nigricollis, S. plumbea, S. leucoptera, S. collaris, S. angolensis and S. caerulescens, in order of abundance. S. nigricollis and S. plumbea can be considered generalists on microhabitats and food items and overlap more their niche than those of others. They showed mechanisms to mitigate the competition, as changes in the use of vertical strata. The distribution of S. leucoptera, resident species, was more related to michohabitats quality, with preference for the inner part of most preserved, complex and heterogeneous palm swamps, with sparse palms and large shrub-tree portion. S. collaris occurrence was more related to presence of adequate food, which is in agreement with fact that migratory species inhabits the region for food during the dry months and the likely food shortage in their reproduction areas. S. caerulescens and S. angolensis were not abundant. The occurrence of the first was in a degraded area, while the second was restricted to a preserved section of palm swamp with plenty of water tank, along with a riparian vegetation fragment, that was used by an adult and a young male, which represents the possibility of using the point to reproduction. The points which have microhabitats more preserved, complex and heterogeneous, in general, bore a greater number of species and individuals. The microhabitats in areas altered by conversion to pasture, despite being in regeneration process and having some native grasses species, hardly been used by Sporophila spp., even the less demanding species, which reinforces the importance of conservation of palm swamp areas and its surroundings to maintain these species. The species studied were morphometrically different, not only in total length, but in relation to other body structures, as in beak and tarsus size, which leads to strong changes in shape, probably as result of adaptive different forms of environmental use.